(untitled) (Bangladesh Journal of Microbiology, 2016)
Microbial fungal cellulases are very important for their applications in biopolishing of textile fibres, in poultry feed and paper and pulp industries. The main purpose of this study was to improve the wild strain Trichoderma viride for enhanced production of cellulase by random mutation technique employing ultraviolet (UV) irradiation and Ethidium bromide (EtBr) treatments. The wild strain exhibited the highest cellulase activity 5.52 U/ml on carboxy methyl cellulose (1.0%) and a comparable activity 4.74 U/ml on wheat bran (1.0%) as substrate under the optimum temperature 30°C and pH 4.0. Upon mutation by UV exposure the fungi produced cellulase 11.28 U/ml where as EtBr treated mutant showed 14.61 U/ml cellulase activities. Both the enzymes from wild and mutant T. viride demonstrated the highest activity at the assay temperature of 40ºC. The enzyme was applied for bio-polishing of jeans at prototype experiment and showed effective result as compared to one of the commercial enzymes. Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 43-47